2002
DOI: 10.1007/s00276-002-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the length of the human intestine

Abstract: Although preoperative assessment of the length of the intestine may be of interest to avoid postoperative consequences of large intestinal resection, measurements of the intestine are quite rare and results variable in the literature. This anatomical study aimed to assess the length of the different intestinal segments, their variation and their correlation with sex, age, weight and height. Two hundred non-fixed adult cadavers (100 men, 100 women) who willingly gave their bodies for scientific purposes were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(33 citation statements)
references
References 0 publications
7
25
0
1
Order By: Relevance
“…In the standard diagram shown in Figure 15, the total length of the lower gastrointestinal tract is represented as 150 cm, with the colon (from the cecum to the rectosigmoid junction) being 130 cm. This is consistent with the lengths of colon measured in living individuals (reviewed in [36]). From our observations of 32 resected colon segments, with 12 in the ascending colon, 6 in the transverse colon and 14 in the descending/sigmoid colon (Table 2) and taking an average of the inner circumferences of the three regions, we determined that 6.2 cm is the average inner circumference of the colon (see Figure 13 for how inner circumferences were measured, after colon segments were opened longitudinally).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the standard diagram shown in Figure 15, the total length of the lower gastrointestinal tract is represented as 150 cm, with the colon (from the cecum to the rectosigmoid junction) being 130 cm. This is consistent with the lengths of colon measured in living individuals (reviewed in [36]). From our observations of 32 resected colon segments, with 12 in the ascending colon, 6 in the transverse colon and 14 in the descending/sigmoid colon (Table 2) and taking an average of the inner circumferences of the three regions, we determined that 6.2 cm is the average inner circumference of the colon (see Figure 13 for how inner circumferences were measured, after colon segments were opened longitudinally).…”
Section: Resultssupporting
confidence: 90%
“…The inner longitudinal dimension of the freshly obtained, non-fixed human colon (from 100 male and 100 female cadavers, measured a few hours after being brought to the laboratory, or after the intestinal tracts were preserved in a refrigerator at 3°C for 24-72 hours) is, on average, 160.5 cm (measured from the bottom of the cecum to the colorectal junction) with a range of 80 cm to 313 cm [36]. The intestine lengthens after death, possibly because of loss of intestinal muscular tone (reviewed in [36]). Thus, a 160.5 cm length is consistent with the length shown in Figure 15, representing the living colon.…”
Section: Resultsmentioning
confidence: 99%
“…Colon lengths may vary over 2-fold [16], allowing for the variation predicted with the equation. This example indicates how a small biological feature ( m or the number of crypts) is interrelated with cancer risks and can be indirectly measured from cancer epidemiology.…”
Section: Resultsmentioning
confidence: 99%
“…Khashab et al 8. measured CT regional volumes of an insufflated bowel and found an increase in the length of transverse colon with age and female gender, Postmortem studies are hard to interpret5 while measurements from barium enema7 are likely to be influenced by the volume infused which depends on patient tolerance. This study found that the total length of colon was longer in females (and female colon lengths tended to increase with height and weight), and tendency to increase with age for both genders.…”
Section: Discussionmentioning
confidence: 99%
“…To date, measurements of regional colon dimensions have mainly been obtained from resected cadaver specimens,4,5 interoperative measurements6 or from radiological assessments of the prepared, distended colon during barium examination7 or CT colonoscopy 8. All these methods disturb the natural morphology of the bowel.…”
Section: Introductionmentioning
confidence: 99%